A conceptual model of green it practices on organisational sustainability - Abdul Kader Jailani, Sri Fatiany; Abdullah, Lili Marziana; Kartiwi, Mira; Hussin, Husnayati (IEEE, 2016)
Green IT practice is not new term word in business organisation and has actually spread in practice and application witnessing people working on the bright side of it. Green IT typically collaborates strongly with the environment. However, this paper removes itself from merely focusing on that perspective. In the context of this study, organisational sustainability is viewed based on three perspectives: - which are economic, social and environmental (Triple Bottom Line index). These three factors are considered as the primary function of this research. Finally, this paper attempts to investigate, whether the implementation of Green IT practice benefits and leads to organisational sustainability.